Pendampingan Minat Baca Anak melalui Pengoptimalan Rumah Ilmu di Desa Sambirejo Kecamatan Jiwan Kabupaten Madiun - Izzatul Ilmiyah; Ika Nazilatur Rosida; Ahmad Muzakki; Dhika Leo P (STAI Senori Tuban, 2025)
Reading interest is one of the important indicators in improving the quality of human resources from an early age. However, the reality in the field shows that children's literacy culture, especially in rural areas such as Sambirejo Village, Jiwan District, Madiun Regency, is still relatively low. This community service activity aims to foster and develop children's reading interest by optimizing the function of Rumah Ilmu as a community-based literacy center. The approach used is Asset-Based Community Development (ABCD), which is a community empowerment approach that focuses on local strengths and potential. Activities are carried out through five main stages: discovery (identification of assets), dream (formulation of community expectations), design (action planning), define (program implementation), and destiny (evaluation and sustainability). The results of the activity show that strengthening the function of Rumah Ilmu is able to increase children's participation in routine reading activities, encourage community involvement, and create an inclusive and sustainable literacy space. The relocation of Rumah Ilmu to a more strategic location and a creative and fun mentoring approach are the keys to the success of this activity. With the support of local volunteers and active participation of residents, Rumah Ilmu has succeeded in becoming an agent of change in building a culture of literacy from an early age